RISK-BASED AUDITING IN PRACTICE: A SYSTEMATIC REVIEW OF IMPLEMENTATION AND IMPACT - Ahmed , Ebrahim Mohammed; Japee , Gurudutta P. (International Journal of Accounting & Finance Review, 2025)
As companies look to align audit processes with risk exposure rather than solely with compliance, risk-based auditing (RBA) has become increasingly important in contemporary auditing. Nevertheless, despite its theoretical advantages, RBA's actual application remains uneven, and its efficacy varies across industries and audit settings. This study's objective is to methodically investigate the practical application of RBA and assess its quantifiable effects on audit performance using the available empirical data. This study screens peer-reviewed journal papers published between 2010 and 2024 using a systematic literature review process that adheres to PRISMA principles. To evaluate implementation tactics, operational difficulties, and quantitative results about RBA adoption, a total of 23 qualifying papers were examined. The findings show that RBA implementation is rising worldwide, especially among regulated businesses, public bodies, and financial institutions. Improvements in audit effectiveness and operational efficiency are demonstrated by quantitative evidence from the reviewed studies, including quantifiable reductions in audit time reported in 7 studies, increases in risk-prioritization accuracy in 9 studies, and improvements in audit resource-allocation efficiency documented in 6 studies. Compared with conventional audit techniques, several studies also demonstrate improved identification of high-risk audit concerns. The main conclusions show that RBA adoption strengthens audit decision-making, increases assurance quality, and improves alignment between audit operations and organizational risk exposure. However, the data also show that differences in organizational preparedness, audit maturity, and training quality affect performance and implementation outcomes.JEL Classification Codes: M42, M48, G32, C83.